Neue Sachlichkeit 1920-1933. (Köln : Galerie Rudolf Zwirner, 1966)
Bissier, Julius ; Davringhausen, Heinrich ; Dressler, August W. ; Fritsch, Ernst ; Grossberg, Carl ; Grosz, George ; Hubbuch, Karl ; Jürgens, Grethe ; Mertens, Hans ; Radziwill, Franz ; Schad, Christian ; Schlichter, Rudolf ; Schrimpf, Georg ; Viegener, Eberhard ; Wegner, Erich ; Wunderwald, Gustav
Duits
boek
Keywords: Duitsland